2014
DOI: 10.1103/physrevlett.113.240403
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Berry Phase by the Trajectories of Majorana Stars

Abstract: The Majorana's stellar representation, which represents the evolution of a quantum state with the trajectories of the Majorana stars on a Bloch sphere, provides an intuitive way to study a physical system with a high dimensional projective Hilbert space. In this Letter, we study the Berry phase by these stars and their loops on the Bloch sphere. It is shown that the Berry phase of a general spin state can be expressed by an elegant formula with the solid angles of Majorana star loops. Furthermore, these result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 36 publications
0
56
0
Order By: Relevance
“…It is easy to verify the commutation relations for spin operators: [F i , F j ] = i ijk F k . Now the spin-1 state |ψ can be factorized as [58][59][60][61][62][63]…”
Section: Proof Of |C| ≤ 2 For Tdps Of Linear Hamiltoniansmentioning
confidence: 99%
“…It is easy to verify the commutation relations for spin operators: [F i , F j ] = i ijk F k . Now the spin-1 state |ψ can be factorized as [58][59][60][61][62][63]…”
Section: Proof Of |C| ≤ 2 For Tdps Of Linear Hamiltoniansmentioning
confidence: 99%
“…The Majorana representation is used to determine geometric phase of spins (cf. [22,23]), in studying the symmetries of spinor Bose-Einstein condensates (cf. [24][25][26]), in geometrical representation of multi-qubit entangled states (cf.…”
Section: Introductionmentioning
confidence: 99%
“…The Majorana representation (MR), in which a pure state of a spin- system 1 , 2 can be precisely described as the trajectory of stars on a unit sphere, was proposed by Majorana in 1932 3 . Over the past decades, the MR has been proved to be a valuable method for many applications in quantum entanglement 4 10 , Bose-Einstein condensates 12 16 , 25 , and geometric phase 10 , 17 20 . In refs 10 , 20 , the Berry phase was studied by the stars and their loops on the Bloch sphere.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, the MR has been proved to be a valuable method for many applications in quantum entanglement 4 10 , Bose-Einstein condensates 12 16 , 25 , and geometric phase 10 , 17 20 . In refs 10 , 20 , the Berry phase was studied by the stars and their loops on the Bloch sphere. With the solid angles of the Majorana star loops, an intuitive relation between the Berry phase and Majorana stars’ trajectories on the Bloch sphere was given and it was shown that the Berry phase is determined by both the solid angles subtended by every Majorana star’s evolution path and the correlations between the stars 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation